MR Imaging Visualization of the Cerebral Microvasculature: A Comparison of Live and Postmortem Studies at 8 T - Dashner, Roger A.; Chakeres, Donald W.; Kangarlu, Allahyar; Schmalbrock, Petra; Christoforidis, Gregory A.; DePhilip, Robert M. (American Journal of Neuroradiology, 2003)
Summary: In this study, we compared 8-T gradient-echo MR images of the microvasculature in the live human brain with images of the unembalmed and embalmed postmortem brain. Small vessels were well visualized in the live brain and even better seen in the unembalmed postmortem brain, but they could not be visualized in the embalmed postmortem brain. These findings are important for direct comparisons of the microvasculature on 8-T MR images and on histologic sections.